2019
DOI: 10.1371/journal.pone.0208491
|View full text |Cite
|
Sign up to set email alerts
|

The role of intergenerational educational mobility and household wealth in adult obesity: Evidence from Wave 2 of the World Health Organization’s Study on global AGEing and adult health

Abstract: BackgroundObesity has emerged as a major risk factor for non-communicable diseases in low and middle-income countries but may not follow typical socioeconomic status (SES)-related gradients seen in higher income countries. This study examines the associations between current and lifetime markers of SES and BMI categories (underweight, normal weight, overweight, obese) and central adiposity in Ghanaian adults.MethodsData from 4,464 adults (2,610 women) who participated in the World Health Organization’s Study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
(85 reference statements)
1
4
0
Order By: Relevance
“…Upwardly mobile participants were more likely to fall into obesity than participants remaining in stable low social class. The associations observed in our study were consistent with previous studies in low-middle income countries showing positive correlation between life-course SES and obesity(31, 32). For example, a cross-sectional study in five middle-income countries (China, South Africa, India, Russia, and Mexico) found that life-course stable high or declining SES was associated with increased risks of overweight/obesity(31).…”
Section: Discussionsupporting
confidence: 93%
“…Upwardly mobile participants were more likely to fall into obesity than participants remaining in stable low social class. The associations observed in our study were consistent with previous studies in low-middle income countries showing positive correlation between life-course SES and obesity(31, 32). For example, a cross-sectional study in five middle-income countries (China, South Africa, India, Russia, and Mexico) found that life-course stable high or declining SES was associated with increased risks of overweight/obesity(31).…”
Section: Discussionsupporting
confidence: 93%
“…Even though household wealth is sometimes seen as a poor index for household consumption or expenditure, there has been a consistent lack of data in most low-and middle-income countries to measure the long-term economic status [39–42]. In this study, household wealth was constructed using principal component analysis from 22 items that considered assets and the derived variable was indexed into five quintiles [43].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, since the index is relative and country-specific, it does not explain the association of absolute wealth gains (such as savings or debt) across the life course with health outcomes. Such studies have been attempted in a limited way across geographies such as in the analysis of cross-sectional measures of income (such as gross national income per capita adjusted for purchasing power parity) or household wealth with child height and adult overweight ( Karra et al, 2017 ; Lartey et al, 2019 ; Paciorek et al, 2013 ; Templin et al, 2019 ). The positive association between wealth and BMI in adulthood in Guatemala, India and Philippines is consistent with wider literature that suggests countries earlier in the nutrition transition exhibit a positive association between socioeconomic position and BMI ( Templin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%